Confrontaciones: Ayala y los poetas del 27 - Miguel Ángel García (Mélanges de la Casa de Velázquez)
The literary relations between Francisco Ayala and the poets of the Generation of ‘27 have not yet been further explored. This article proposes three points of confrontation, basic to the lyrical identity of this canonical group: the dialectic between tradition and avant-garde, the debt of Gongorism with the concepts of dehumanization and purity, and the practice of a poetic neopopularism that stylizes Andalusian folklore. As an always alert critical conscience, Ayala questions these signs of identity from a position more attached to the avant-garde program. While at the end of the 1920s he discusses the poetic assumptions of authors as central to the Spanish lyrics of the last century as Gerardo Diego, Luis Cernuda and Federico García Lorca, later he accepts the label of «Generation of '27», although he shows that historiographic fortune has smiled at poets and not so much at avant-garde prose writers who, like him, adhered to the forms and contents of the new literature.